2021
DOI: 10.3390/su132212898
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology in Wine Chain for Collecting and Addressing Sustainable Performance: An Exploratory Study

Abstract: Sustainability standards have not yet been commonly adopted by the whole wine chain, and indicator assessments are not widely spread. A deep understanding of how embedding sustainability into business while controlling costs related to the adoption of sustainability certification standards such as data collection and management practices could allow one to overcome most barriers relevant to sustainability compliance. Blockchain technology (BCT) may answer these needs. In order to verify BCT potential to be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…A classical use-case was proposed called from-farmto-fork within the given vertical domain. The two blockchain platforms namely Ethereum and Hyperledger Sawtooth have been utilised to deploy traceable system performances [17]. The performance was analysed with regard to network latency, CPU time, and network usage.…”
Section: Literature Surveymentioning
confidence: 99%
“…A classical use-case was proposed called from-farmto-fork within the given vertical domain. The two blockchain platforms namely Ethereum and Hyperledger Sawtooth have been utilised to deploy traceable system performances [17]. The performance was analysed with regard to network latency, CPU time, and network usage.…”
Section: Literature Surveymentioning
confidence: 99%
“…Although, the applications of blockchain in supply chain management have been widely concerned, many researches concentrated on the levels of technology and some concepts (Nayak and Dhaigude, 2019; Lahkani et al ., 2020; Lee and Yeon, 2021; Luzzani et al ., 2021; Khan et al ., 2021; Nayal et al ., 2021; Mubarik et al ., 2021). In the blockchain environment, researches about the impacts of blockchain on supply chain operation management were closely related to our research and many efforts had obtained (Choi, 2019; Niu et al ., 2021; Liu et al ., 2021; Jian and Yd, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, consumer and public acknowledgement regarding the material flow and product journey across the value chain are improved (Hasan et al, 2020 ; Köhler & Pizzol, 2020 ). For instance, Luzzani et al ( 2021 ) empirically revealed that the blockchain-enabled collection of transparent information regarding soil and water features, climate condition, treatment with pesticides and fertilizers, production process, traceability, and labour and human rights helped enhance consumers’ trust placed on wine producers, and this was reflected in sales growth. Hence, it is expected that the trustor entity will have more confidence in supply chain commitment and bestow a higher level of trust to the supply chain showing quality data recorded for the whole supply chain process and activities (Cao et al, 2021 ; Li et al, 2020 ).…”
Section: Blockchain and Trust In Supply Chainsmentioning
confidence: 99%